Edukasi Dan Pelatihan SADARI (Pemeriksaan Payudara Sendiri) Sebagai Upaya Pencegahan Kanker Payudara Pada Remaja Putri - Hasrita Octaliana (Universitas Muhammadiyah Malang, 2026)
Purpose – This community service aims to improve the knowledge, skills, and soft skills of female adolescents in conducting early detection of breast cancer through breast self-examination (BSE), enabling them to perform it independently at home and respond appropriately when symptoms are found, thereby contributing to the reduction of breast cancer incidence. Design/methodology/approach – The activity was carried out in several stages: initial pre-test, followed by education and hands-on training on BSE, and concluded with a post-test to assess the improvement in participants' knowledge. Findings – The results of the community service showed a significant increase in participants' knowledge of BSE as a breast cancer prevention effort. Before the intervention, approximately 70% of participants had good knowledge, which increased to 100% after the program. This represents a 30% increase, exceeding the ≥20% effectiveness benchmark, indicating the intervention was highly effective, with more than 80% of female adolescents demonstrating good knowledge. Originality/value – The BSE education and training activity for high school female students has significant implications for increasing early breast cancer detection awareness through a school-based, participatory, and combined method approach, offering a novel, relevant, and practical strategy for implementation among adolescents from an early age.